Gender differentials in the timing and prognostic factors of pubarche in Nigeria (2022)
Paucity of data exists on the timing of puberty, particularly the pubarche, in developing coun tries, which has hitherto limited the knowledge of the timing of pubarche, and assistance offered by physicians to anxious young people in Nigeria. Factors associated with the timings of puberty and pubarche are not well documented in Nigeria. We hypothesized that the timing of pubarche in Nigeria differs by geographical regions and other characteristics. We assessed the timing of pubarche among adolescents and young adults in Nigeria and identified prognostic factors of the timing by obtaining information on youths’ sexual and reproductive developments in a population survey among in-school and out-of-school youths aged 15 to 24 years in Nigeria. A total of 1174 boys and 1004 girls provided valid information on pubarche. Results of time-to-event analysis of the data showed that mean age at pubarche among males aged 15 to 19 years and 20 to 24 years was 13.5 (SD = 1.63 years) and 14.2 (SD = 2.18 years) (respectively) compared with 13.0 (SD = 1.57 years) and 13.5 (SD = 2.06 years) among females of the same age. Median time to pubarche was 14 (Interquartile range (IQR) = 3) years and 13 (IQR = 3) years among the males and females, respectively. Cumulatively, 37% of the males had attained pubarche by age 13 years versus 53% among females, 57% vs 72% at age 14, and 73% vs 81% at age 15. The likelihood of pubarche among males was delayed by 5% compared with females (Time Ratio (TR) = 1.05: 95% CI = 1.03–1.05). Every additional one-year in the ages of both males and females increases the risk of pubarche by 1%. Similar to the females, males residents in Northeast (aTR = 1.14, 95% CI: 1.07–1.21), in the Northwest (aTR = 1.20, 95% CI: 1.13–1.27) and in the Southwest (aTR = 1.18, 95% CI: 1.11–1.26) had delayed pubarche than males from the South East. Yoruba males had delayed pubarche than Ibo males (aTR = 1.06, 95% CI: 1.01–1.12). Age at pubarche among adolescents and young adults in Nigeria differed among males and females with earlier onset among females. Pubarche timing varied mainly by ethnicity, region, and location of residence. Our findings will aid medical practitioners in providing appropriate advice and support on pubarche-related issues among adolescents in Nigeria as it could help douse pubarche anxiousness in relation to request for medical assistance.